Secularization of Serat Centhini in the Context of Creative Industries - Tjahjandari, Lily; Setyani, Turita Indah (MOZAIK HUMANIORA, 2024)
Serat Centhini is one of the greatest literary works in New Javanese Literature, written around 1742 (Javanese Year) or 1814, containing a collection of various knowledge related to Javanese Culture. Serat Chentini’s greatness has been sought to be preserved to the present in the form of adaptations, both in the form of adaptations, both in the form of lyrical prose, novels and even into the 21st century, it has been translated into soap operas and television shows. Serat Centhini is considered a reference to the spirituality of Javanese society, namely Javanese Sufism. This article discusses the secularization of Serat Centhini in the process of transferring its vehicle to the musical performance art ‘Serat-serat Centhini’ by the Hip Hop music Group ‘Kill The DJ’ (2011) and the Dance ‘Centhini Gunung’ (2016) as a product of creative industry. Through this two adaptations, Serat Centhini is represented in the contemporary context that contains a tension between sexuality and spirituality. The research results show that there is a process of secularization of religious values in the transformation of the two texts over vehicles to support the creative industry context, so that things that refer to religious values appear profane.